Spatial distribution of daily and monthly precipitation in the Central Caribbean side of Costa Rica - Quesada Quesada, Marvin Elí (2023)
The spatial variations of trends of relevant monthly and daily precipitation, as the probability of wet or dry conditions is taken into consideration to see the amount of precipitation per station. The research examined six rainfall stations in the Caribbean slope of Costa Rica in a period between 1989 to 2019. The research uses the rain data provided for a National Meteorological Institute (IMN) and the figures were made using ArcGIS. This study aims to consider the amount of precipitation, the mean daily, monthly, total rainfall, probability of wetness, monthly maximum daily precipitation, and deviations in monthly total precipitation from average. It was shown how on the Caribbean side some months have an opposite answer depending on the ENSO phase. Each station has different answer depending on their location and the month. For instance, certain months like March, April and October present some dryness. The research reflects that in the Caribbean slope of Costa Rica the warm phase behaves in different way in the same region, even though this is somehow flat. Although, Costa Rica is a small country (51.179km²) is far from being uniform, and the results presented in this research reveal differences in the daily and monthly rain. In the Caribbean slope the ENSO phases increase impact in monthly and daily circulations over the Atlantic through the Jet streams (CLLJ).